Pengaruh Motivasi Belajar, Penyalahgunaan Teknologi Informasi dan Integritas Mahasiswa Terhadap Prilaku Kecurangan Akademik Mahasiswa Akuntansi Sebagai Calon Akuntan - Rahmawati, Fina; Gantino, Rilla (Asosiasi Dosen Akuntansi Indonesia, 2023)
Where student learning motivation can affect student academic cheating behavior, it occurs because of a lack of interest in learning from students. Misuse of information technology affects student academic cheating behavior, it occurs because students are lazy to read books and repeat lessons that have been taught by their lecturers only relying on technology as a reference material to get the results of the exam. Student integrity can affect student cheating such as feeling confident with the cheating they do to get good results but in reality they rarely get perfect results. The sample used in this research is saturated sampling ie 67 accounting students at the Institute of Technology and Business Haji Agus Salim Bukittinggi. This research data is primary data because here the author uses a questionnaire directly to the object of research, namely accounting students at the Haji Agus Salim Institute of Technology and Business Bukittinggi. The data analysis technique used in this study is data in the form of numbers that can calculated accurately (definitely) based on SPSS. The results show that student academic fraud is obtained from misuse of information technology, and student integrity.